Optimization of ultrasound-assisted-extraction of porcine placenta water-soluble proteins and evaluation of the antioxidant activity - Tang, W.; Zhang, M.; Fang, Zhongxiang (2014)
Porcine placenta is commonly used in Chinese as a traditional medicine. It has been reported by a number of researchers that the porcine placenta contains many compounds which have good health benefits. Response surface methodology (RSM) was applied to optimize the parameters of ultrasound power, ultrasound treat time, and extraction temperature on the extraction yield of porcine placenta water-soluble proteins (PPWP). The results indicated that, under optimum conditions of ultrasound power 257 w, extraction temperature at 49 °C for 7 min, the extraction yield of PPWP was 32.7%, which was significantly higher than that of the conventional extraction method (CEM) of 15.0 %. The experimental data were fitted to a second-order polynomial equation using multiple regression analysis and the estimated model showed a high capacity of predicting the dependent variables. Although not significantly, the antioxidant activity of PPWP from ultrasound-assist-extraction (UAE) were higher than those from CEM, indicated that UAE had a positive effect or at least no negative effect on the bioactivity of PPWP.